Formulation of Mouth Mouth From Ethanol Extract of Carrot (Daucus Carota L.) Tubes as an Antifungal Against The Growth of Candida Albicans - Diana, Vivi Eulis; Abadi, Hafizhatul (International Archives of Medical Sciences and Public Health, 2023)
One of the causes of canker sores and bad breath is the presence of fungus in the oral cavity. This can be overcome by gargling using mouthwash. Research has been carried out on the formulation of mouthwash preparations from ethanol extract of carrot (Daucus carota L.) tubers as an antifungal against the growth of Candida albicans. Objectives: The aim of this study was to see the antifungal activity of carrot tuber extract mouthwash preparations. Methods: This research is a type of laboratory experimental research using the paper disc diffusion method on agar media to see the antifungal activity of carrot root extract mouthwash preparations. Carrot tuber extract mouthwash was made into four formulas, namely F0 (preparation without extract), F1 (5% carrot extract), F2 (15% carrot extract) and F3 (30% carrot extract). Evaluation of mouthwash preparations includes examination of organoleptic, pH, viscosity and stability. Results: indicate that mouthwash preparations can provide antifungal activity against the growth of Candida albicans. The diameter of the inhibition zone obtained at concentrations of 5% (2.9 mm), 15% (3.9 mm) and 30% (5.3 mm). All mouthwash formulations have a weak category of inhibitory power. The results of organoleptic evaluation, pH, viscosity and stability of mouthwash preparations gave good results, were stable and fulfilled the requirements for mouthwash preparations. Conclusion is that the ethanol extract of carrot root can be formulated into mouthwash and has weak antifungal activity.